2017
DOI: 10.1088/1612-202x/aa7d37
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy–based screening of hepatitis C and associated molecular changes

Abstract: This study presents the optical screening of hepatitis C and its associated molecular changes in human blood sera using a partial least-squares regression model based on their Raman spectra. In total, 152 samples were tested through enzyme-linked immunosorbent assay for confirmation. This model utilizes minor spectral variations in the Raman spectra of the positive and control groups. Regression coefficients of this model were analyzed with reference to the variations in concentration of associated molecules i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…2, section 3.1.) and also show agreement with [34,37] and Bilal et al, findings which have reported the correlation of 718, 872, 1004, 1169, 1250 cm −1 with HCV infection [36].…”
Section: Decision Surface Based Analysis Of Raman Shifts and Its Biocsupporting
confidence: 91%
See 1 more Smart Citation
“…2, section 3.1.) and also show agreement with [34,37] and Bilal et al, findings which have reported the correlation of 718, 872, 1004, 1169, 1250 cm −1 with HCV infection [36].…”
Section: Decision Surface Based Analysis Of Raman Shifts and Its Biocsupporting
confidence: 91%
“…Mannose-binding lectin is one such molecule which on attachment with virus mediates lectin complement pathway that kills virus [35]. 1169 cm −1 peak corresponds to lipids where 1250 cm −1 is assigned to ammonia whose level increases in infected individuals, as liver damaged by HCV infection fails to detoxify ammonia [36]. Lipids are associated with proteins that stimulate destruction process of hepatocytes.…”
Section: Decision Surface Based Analysis Of Raman Shifts and Its Biocmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS), with advantages in high sensitivity and specificity, is rapidly expanding its applications in biochemical and biomedical analysis [5][6][7]. When gold or silver nanoparticles are transferred into living cells, SERS signal can be measured by the light interaction with the intracellular biochemical components and nanoparticles [8,9] and provides a powerful tool for sensitive detection of intracellular biological macromolecules (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are several new techniques to solve this problem, such as the fiber-endoscopy with auto fluorescence, aminolaevulinic acid-induced fluorescence, confocal endomicroscopy, etc. Among them, Raman spectroscopy (RS) technology attracts broad attention for its convenience, sensitivity and objectiveness [3][4][5]. RS, a technology based on proton inelastic scattering process, was first described by Raman in 1928.…”
Section: Surface-enhanced Raman Spectroscopy For Classification Of La...mentioning
confidence: 99%